The Evolution of Design Thinking in the Age of Foundation Models: Revisiting Verganti’s Framework (2020-2025) - Del Giorgio Solfa, Federico (2025)
This article offers a critical tribute to “Innovation and Design in the Age of Artificial Intelligence”, which anticipated the shift from problem solving to problem finding as the key human role in design under algorithmic automation. Five years later, this paper revisits and expands that framework amid three major transformations: the rise of foundation models and generative AI, the emergence of agentic artificial intelligence capable of orchestration, and the institutionalization of governance through the European AI Act and ISO/IEC 42001. Revisiting Netflix, Airbnb, Tesla, and Microsoft, the study proposes the Agentic Orchestrator Model, integrating four interdependent layers—governance, human sensemaking, agentic orchestration, and operational loops. This model repositions design as a continuous socio- technical architecture where humans, agents, and norms co-produce value and responsibility, extending Verganti’s insights into the era of generative and regulated AI.